INTEGRATION OF COLLABORATIVE LEARNING STRATEGIES INTO VOCATIONAL EDUCATION IN FEDERAL COLLEGE OF EDUCATION (TECHNICAL) GUSAU, NIGERIA - APITYAN TUME (International Studies Journal)
This study explores the integration of collaborative learning strategies into vocational education at the Federal College of Education (Technical) Gusau, Nigeria. The questionnaire served as the primary data collection tool. Out of 112 distributed questionnaires, 100 were returned and analyzed. Data were quantitatively analyzed using frequency counts, percentage distribution tables, mean, and standard deviation, with a benchmark mean of 1.5. The findings indicate that collaborative learning positively impacts teamwork and practical skills, with mean scores of 1.67 and 1.66, respectively. However, there is some uncertainty regarding its effectiveness in enhancing vocational understanding, as reflected by a mean score of 1.56, and mixed opinions on motivation for team activities, with a mean score of 1.60. The study also demonstrates that collaborative learning significantly improves students' skills in vocational education by enhancing their understanding, problem-solving abilities, and engagement. The study recommends enhancing the clarity and structure of collaborative activities, increasing student motivation with engaging projects, training instructors in effective facilitation techniques, and regularly evaluating and adapting strategies to improve outcomes.